2014 Oceans - St. John's 2014
DOI: 10.1109/oceans.2014.7003084
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost coastal mapping using Kinect v2 time-of-flight cameras

Abstract: High-resolution elevation and bathymetry data for coastal zones is extremely valuable to many researchers, however the cost of acquiring such data is prohibitively expensive for most research budgets, as it relies on specialized hardware. Mass produced off-the-shelf consumer cameras and sensors are becoming increasingly powerful, and can be affordable alternatives for collecting data. Microsoft's original Kinect sensor was repurposed to collect data for Earth sciences research, but its low depth resolution hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 11 publications
2
37
0
Order By: Relevance
“…The resolution for color camera which is 1920*1080 is also higher than the previous version of Kinect, but the accuracy of depth which is taken by Kinect V2 is found to be the same as the first version (the standard deviation of depth is less than 3.5 mm at 4.5 meters' distance) (Khoshelham & Elberink 2012). The color camera's field of view is a bit more than a depth image (84.1 degrees in Horizontal and 53.8 degrees in Vertical) (Butkiewicz 2014). The Kinect V2 has a features that can map the pixels from color image to pixels from depth image.…”
Section: Kinect V2mentioning
confidence: 85%
See 4 more Smart Citations
“…The resolution for color camera which is 1920*1080 is also higher than the previous version of Kinect, but the accuracy of depth which is taken by Kinect V2 is found to be the same as the first version (the standard deviation of depth is less than 3.5 mm at 4.5 meters' distance) (Khoshelham & Elberink 2012). The color camera's field of view is a bit more than a depth image (84.1 degrees in Horizontal and 53.8 degrees in Vertical) (Butkiewicz 2014). The Kinect V2 has a features that can map the pixels from color image to pixels from depth image.…”
Section: Kinect V2mentioning
confidence: 85%
“…Khoshelham and Elberink in 2012 showed that by increasing the distance between Kinect and the surface, the random error of depth measurement will increase quadratically from a few millimeters to 4 centimeter (in the 5 meter distance) (Khoshelham & Elberink 2012). The tool is so cheaper for collecting RGB-D data rather than similar tools like Laser sensors which cost up to several thousand dollars (Yang & Diez-Roux 2012;Butkiewicz 2014). It can record up to 30 frames per second which equals to saving more than 540 million pixels per minute (30Hz frequency).…”
Section: A Novel Approach Kinectmentioning
confidence: 99%
See 3 more Smart Citations